The Burden of Spinal Disorders in the Elderly. (October 2015) - Waldrop, Robert; Cheng, Joseph; Devin, Clinton; McGirt, Matthew; Fehlings, Michael; Berven, Sigurd
Abstract : Disorders of the spine are common and have a significant and measurable burden on affected patients and on our healthcare economy. The burden of spinal disorders encompasses metrics such as the prevalence of spinal disorders, the impact of spinal disorders on health-related quality of life, and the use of resources associated with the operative and nonoperative management of spinal disorders. Measurement of the burden of spinal disorders is important in prioritizing the distribution of limited resources within our healthcare economy. In 1998, the Priority Setting Committee of the Institute of Medicine concluded that in defining health priorities for research and funding, the burden of disease and impact on the health of the population should be the primary determinants of resource allocation. The purpose of this article is to report metrics comprising the burden of spinal disorders, with a focus on the significant and growing burden of spinal disorders in our elderly population, and to demonstrate that allocation of resources to the management of spinal disorders should be a priority for our healthcare economy.